Prevalence of Urinary Schistosomiasis among School Aged Children in Bakura Local Government Area of Zamfara State Nigeria - Mudassiru, I.; Suleiman, A. B.; Dibal, D. M.; Abdulhamid, Y.; Abba, A. M. (UMYU Journal of Microbiology Research)
Urinary schistosomiasis (Bilharziasis) is a parasitic disease caused by digenic trematode called Schistosoma haematobium, it is a water based parasitic disease transmitted by water snails of the genus Bulinus that mainly affect children. A study was carried out to determine the prevalence of Urinary Schistosomiasis among School aged children of three selected communities in Bakura LGA of Zamfara State to determine the prevalence of S. haematobium from urine samples of the pupils and to relate the prevalence of infection with socio- demographic factors such as age, sex and water contact activities of the sampled subject. A total of 360 urine samples comprising of 120 each from the Yargeda, Kwanar Kalgo and Tungar Maiburtu Primary Schools were collected and examined by sedimentation technique for the presence of S. haematobium eggs. The overall percentage of infection recorded was 30.0% while percentages of infection obtained among the selected Primary Schools were 33.3%, 16.7% and 40.0% in Yargeda, Kwanar Kalgo and Tungar Maiburtu respectively. Male pupils recorded the highest rate of infection (44.9%) than female pupils (23.6%). Age group 8-11 years old had highest infection rate (35.7%), while the age group 12-15 years had the least prevalence rate (23.5%). In relation to sources of drinking water, pupils with rivers/streams as their main sources of drinking water recorded the highest rate of infection (38.7%), whereas those using tap/bore-hole water had the least prevalence of infection (18.2%). Based on water contact activity, pupils whose water contact activity was mostly fishing had the highest rate (41.4%), while lowest rate of infection of 18.0% was observed among pupils swimming in rivers. In all the cases, chi-square analysis showed no significant association between the rate of infection and water contact activities (P<0.01). Since infection with S. haematobium had been established in the study area, there is therefore a need for public health campaign among pupils to adapt preventive measures with control programs for snails’ intermediate host.